Fauna and predator-prey relationships of Ettling, an actinopterygian fish-dominated Konservat-Lagerstätte from the Late Jurassic of southern Germany. - Martin Ebert; Martina Kölbl-Ebert; Jennifer A Lane (PLoS ONE)
The newly recognized Konservat-Lagerstätte of Ettling (Bavaria), field site of the Jura-Museum Eichstätt (JME), is unique among Late Jurassic plattenkalk basins (Solnhofen region) in its abundant, extremely well preserved fossil vertebrates, almost exclusively fishes. We report actinopterygians (ginglymodins, pycnodontiforms, halecomorphs, aspidorynchiforms, "pholidophoriforms," teleosts); turtles; and non-vertebrates (echinoderms, arthropods, brachiopods, mollusks, jellyfish, sponges, biomats, plants) in a current faunal list. Ettling has yielded several new fish species (Bavarichthys incognitus; Orthogonikleithrus hoelli; Aspidorhynchus sanzenbacheri; Macrosemimimus fegerti). Upper and lower Ettling strata differ in faunal content, with the lower dominated by the small teleost Orthogonikleithrus hoelli (absent from the upper layers, where other prey fishes, Leptolepides sp. and Tharsis sp., occur instead). Pharyngeal and stomach contents of Ettling fishes provide direct evidence that Orthogonikleithrus hoelli was a primary food source during early Ettling times. Scarcity of ammonites and absence of vampyromorph coleoids at Ettling differ markedly from the situation at other nearby localities in the region (e.g., Eichstätt, Painten, Schamhaupten, the Mörnsheim beds), where they are more common. Although the exact biochronological age of Ettling remains uncertain (lack of suitable index fossils), many Ettling fishes occur in other plattenkalk basins of Germany (e.g., Kelheim) and France (Cerin) dated as Late Kimmeridgian to Early Tithonian (eigeltingense horizon), suggesting a comparable geologic age. The Ettling deposits represent an independent basin within the larger Upper Jurassic "Solnhofen Archipelago", a shallow subtropical sea containing scattered islands, sponge-microbial and coral reefs, sandbars, and deeper basins on a vast carbonate platform along the northern margin of the Tethys Ocean.